HASIL OKRA DENGAN PEMBERIAN ABU TEMPURUNG KELAPA PADA MEDIA GAMBUT - Surachman; Elly Mustamir (Program Studi Agroteknologi INSTIPER, 2018)
The research aims to find out the best doses of coconut kneecap ash to the growth and yield of okra plant on peat soil. This study was conducted at the experimental sites of The Agricultural Faculty, Tanjungpura University, Pontianak from March 27th to May 24th 2017. The location lies on about 2 meters above sea level. This research used the completely randomize design (CRD) with 5 treatments and 5 replications. Each experiment unit consisted of 4 sample plants. The treatments were the coconut kneecap ash with 5 doses levels e.i. a1 = 1240 g/polybag, a2 = 1260 g/polybag, a3 = 1280 g/polybag, a4 = 1300 g/polybag, a5 = 1320 g/polybag. The result shows that the ash doses significantly influence the growth and yield of okra plant on the peat soil. The dose of the 1300 g/polybag is the best treatment on the shoot weight (4,75 g), the root volume (15,99 ml), the total leaf area per plant (37,49 cm2 ), flowering period (34,13 days), the number of fruit per plant (11,73 fruit) and the weight of fruits per plant (256,60 g). Keywords : Coconut kneecap ash, peat soil, okra plants.